Comparison of prasugrel and ticagrelor in patients with acute coronary syndrome undergoing percutaneous coronary intervention: A meta-analysis of randomized and non-randomized studies. (15th December 2017) - Watti, Hussam; Dahal, Khagendra; Zabher, Henock G.; Katikaneni, Pavan; Modi, Kalgi; Abdulbaki, Abdulrahman
Abstract: Background: The newer oral P2Y12 receptor antagonists (i.e. prasugrel and ticagrelor) are recommended over clopidogrel for patients with acute coronary syndrome (ACS) going for percutaneous coronary intervention (PCI). As the superiority of one agent over the other remains unclear, we designed a systematic review and meta-analysis of these agents in patients with ACS undergoing PCI. Methods: PUBMED, EMBASE, Cochrane CENTRAL, CINAHL and manual search were performed through 11/02/2016. Mortality, myocardial infarction (MI), stroke, repeat revascularization, stent thrombosis (ST) and BARC bleeding ≥ 2 were the major outcomes. Results: A total of 9 studies with 21, 360 total patients were included in the meta-analysis. Compared to ticagrelor, prasugrel was associated with lower rate of MI [0.8% vs. 1.9%; 0.54 (0.29–0.99); P  = 0.05] but no difference was noted in mortality [2.1% vs. 2.4%; 0.84 (0.64–1.09); P  = 0.19], repeat revascularization [1.6% vs. 2.1%; 0.82 (0.61–1.10); P  = 0.19] and stroke [0.2% vs. 0.3%; 0.68 (0.25–1.83); P  = 0.44] between two agents. In addition, prasugrel was associated with lower risk of BARC ≥ 2 bleeding [2.5% vs. 3.8%; 0.75 (0.59–0.95); P  = 0.02] and showed a trend toward a lower risk of ST [0.3% vs. 0.6%; 0.55 (0.28–1.07); P  = 0.08] in comparison with ticagrelor. Conclusions: Based on this meta-analysis of observational and randomized studies, prasugrel appears to be equivalent or superior to ticagrelor in patients with ACS undergoing PCI on the 30-day follow up. Larger randomized trials with longer follow-ups are needed to establish superiority of one agent over the other.